2009
DOI: 10.1158/1078-0432.ccr-09-0826
|View full text |Cite
|
Sign up to set email alerts
|

An miR-502–Binding Site Single-Nucleotide Polymorphism in the 3′-Untranslated Region of the SET8 Gene Is Associated with Early Age of Breast Cancer Onset

Abstract: Purpose: MicroRNAs regulate gene expression by binding to the 3′-untranslated region (UTR) of target genes. Single-nucleotide polymorphisms of critical genes may affect their regulation by microRNAs. We have identified a single-nucleotide polymorphism within the miR-502 seed binding region in the 3′-UTR of the SET8 gene. SET8 methylates TP53 and regulates genome stability. We investigated the role of this SET8 singlenucleotide polymorphism and in concert with the TP53 codon 72 single-nucleotide polymorphism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 49 publications
(49 reference statements)
10
96
2
1
Order By: Relevance
“…SET8 has been shown to be correlated with a series of human tumors, such as hepatocellular cancer, breast cancer, ovarian cancer, and lung cancer (Song et al, 2009;Ding et al, 2012;Guo et al, 2012;Wang et al, 2012;Xu et al, 2013). However, no studies have demonstrated a correlation between SET8 and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SET8 has been shown to be correlated with a series of human tumors, such as hepatocellular cancer, breast cancer, ovarian cancer, and lung cancer (Song et al, 2009;Ding et al, 2012;Guo et al, 2012;Wang et al, 2012;Xu et al, 2013). However, no studies have demonstrated a correlation between SET8 and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, gastric cancer outcomes may be modified by altering SET8 expression, partly because of its affinity to miR-502. Previous studies have suggested that the single-nucleotide polymorphism, located within the miR-502 binding site in SET8, modulates SET8 expression and contributes to cancer risk and early cancer development (Yu et al, 2007;Song et al, 2009). …”
Section: Factormentioning
confidence: 99%
See 1 more Smart Citation
“…A SNP in a miRNA can have a significant effect on its hybridization to the target sites or can affect the processing of the mRNA. For example, a SNP within the 3 0 UTR of SET8, a methyltransferase that represses p53 activity, generates a new miR-502 binding site and is associated with early breast cancer onset in premenopausal women (140). In a study on the impact of 11 miRNA target site SNPs located in the 3 0 UTR of cancer associated genes, a significant association with familial breast cancer risk was observed (141).…”
Section: Genomic Alternations Of Mirnas Contributing To Breast Cancermentioning
confidence: 99%
“…We previously reviewed SNPs within miRNA binding sites and cancer risk[114], followed by case control studies in this field[108]. Recently, Liang et al [109] reported their findings that miRNA binding site SNPs may impact ovarian cancer predisposition and clinical outcome both individually and jointly with genetic variants in miRNA biosynthesis pathways.…”
Section: Snps Among Mirnamentioning
confidence: 99%